2019
DOI: 10.1111/sum.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conservation tillage drills on soil quality indicators in a wheat–oilseed rape rotation: organic carbon, earthworms and water‐stable aggregates

Abstract: The effects of five conservation tillage drills with crop residue levels covering between 17% and 79% of the soil, and tillage depths ranging from 25 mm to 200 mm, were examined over three years. The tillage systems ranged from a relatively disruptive Farm System to a Low Disruption system, with three intermediate treatments labelled Sumo DTS, Claydon, and Mzuri. The study involved field sites on a clay or clay loam soil, where winter wheat and oilseed rape were grown in rotation. In the clay field, the Mzuri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The very low abundance of EWs under farmers' practices in rice fields was confirmed by Singh et al [29] in which they outlined that EWs were more abundant at the margins of the paddy fields in India, but no EWs were observed inside the fields. Our results were also confirmed by the findings of Giannitsopoulos et al [64] who found that the highest EWs' density (181-228 m −2 ) was achieved under the least destructive tillage, while the most disruptive tillage yielded the lowest densities (75-98 m −2 ).…”
Section: Earthworms' Density and Biomasssupporting
confidence: 91%
See 2 more Smart Citations
“…The very low abundance of EWs under farmers' practices in rice fields was confirmed by Singh et al [29] in which they outlined that EWs were more abundant at the margins of the paddy fields in India, but no EWs were observed inside the fields. Our results were also confirmed by the findings of Giannitsopoulos et al [64] who found that the highest EWs' density (181-228 m −2 ) was achieved under the least destructive tillage, while the most disruptive tillage yielded the lowest densities (75-98 m −2 ).…”
Section: Earthworms' Density and Biomasssupporting
confidence: 91%
“…Several studies reported a significant correlation between soil OC and EWs' abundance [26,42,61,65]. Giannitsopoulos et al [64] estimated that for every 10% increase in crop residue retention on the soil surface, EWs' density could increase by 15 indv. m −2 .…”
Section: Earthworms' Density and Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus earthworm activity can render soil environments that are more amenable to microbial activity and diversity (Eriksen-Hamel et al, 2009). Conservation tillage practices that involve crop residue return to surface soils can increase earthworm numbers by hundreds of thousands per hectare (Barthod et al, 2018;Giannitsopoulos et al, 2020) 5.2. Ecosystem services Soils provide vital ecosystem services, rendering both economic and societal benefits (Adhikari and Hartemink, 2016;Dominati et al, 2010;Pavan and Ometto, 2018;Su et al, 2018).…”
Section: Soil Biodiversitymentioning
confidence: 99%
“…The soil cover protects soil agronomic structure [17]. According to results from eight experimental years, Dekemati et al (2019a) [18] pointed out that deep tine cultivation (DC) provided significantly higher crumb ratio (80.5%) as compared to ploughing (P) (70.0%), however there was no difference between DC and shallow tine cultivation (SC).…”
Section: Introductionmentioning
confidence: 99%